The possibility of applying the modified accrual basis in the registration of fixed assets of service organizations in the public sector: Case Study at Erbil Technical Institute - Safaa nawzad ahmed (QALAAI ZANIST JOURNAL, 2020)
The registration of fixed assets in government service units (non-revenue) is one of the most important problems that have been preoccupied by many regulators interested in the accounting profession. The case study approach was adopted by presenting a proposed model for applying the accrual basis of the fixed assets, calculating the annual depreciation on these assets and preparing the financial position list as the most suitable method for applying in the accounting system used in government units in general and the researched organization in particular. The research has concluded that the fixed assets in the researched organization can be collected, measured and calculated, and this confirms the need to provide the necessary government accounting information associated with the performance of the government and clearly to achieve the objectives expected to be measured accurately to facilitate monitoring and evaluation and show the true image of the government unit through the presentation of the values ​​of its assets along with the values ​​and other activities and make sound decisions about them.